(untitled) (Journal of Enam Medical College, 2023)
Caroli’s syndrome is a rare inherited disorder characterized by multiple segmental cystic or saccular dilatation of the intrahepatic bile duct associated with congenital hepatic fibrosis. Symptoms of Caroli’s syndrome may appear early or late during life and its presentation is highly variable. Portal hypertension followed by development of oesophageal varices is the main consequence of congenital hepatic fibrosis. Up to 60% of Caroli’s syndrome patients are associated with renal involvement. The diagnosis of Caroli’s syndrome mainly depends on histology and imaging method that can show the communication between bile ducts and saccule. Important complication is cholangitis and later may progress to cholangiocarcinoma. For symptomatic Caroli’s syndrome, liver transplantation is the only curative treatment. Here, we report a case of Caroli’s syndrome in a 5½ year old girl admitted in the department of Pediatric Gastroenterology and Nutrition, BSMMU with the complaints of abdominal distension since birth. Her CT scan report showed type V choledochal cyst with large cyst in right lobe of liver and polycystic kidney disease. Endoscopy of upper GIT revealed grade II oesophageal varices and MRCP also suggested Caroli’s disease (Type V choledochal cyst). Finally, she was diagnosed as a rare case of Caroli’s syndrome (Type V choledochal cyst with grade II oesophageal varices with polycystic kidney disease). J Enam Med Col 2021; 11(1): 55-58